The Relationship of Osteoporosis Risk Factors with Bone Mineral Density in Patients Admitted Our Outpatient Clinic in Trabzon - Münevver Serdaroğlu Beyazal; Erhan Çapkın; Mustafa Güler; Haşim Çakırbay; Mehmet Tosun (Galenos Yayinevi, 2016)
Objective: Our aim was to identify the relationship of osteoporosis (OP) risk factors with bone mineral density (BMD) in patients admitted our outpatient clinic in Trabzon. Materials and Methods: Two hundred one patients with OP or osteopenia were included in this study. Sociodemographic characteristics of the patients were recorded and a standardized interview was employed by the researcher physician. BMD values were measured by dual energy X-ray absorptiometry at lumbar spine and femoral neck. Results: The mean age of the patients was 61.47±10.57 years (182 females/19 males). One hundred fifteen patients (57.2%) were osteoporotic and 86 (42.8%) were osteopenic. A significant negative correlation was found between age and femoral neck T scores. The number of pregnancies showed a significant negative correlation with lumbar T scores. Body mass index and daily tea consumption showed a negligible positive correlation with femoral neck T scores. No association was found between age at menarche, age at menopause, total lactation duration, daily calcium intake and T scores of lumbar spine and femoral neck. Conclusions: Identification of regional OP risk factors may be useful for the OP risk management of patients in clinical practice.